Metabolomics-driven discovery of an introduced species and two Malaysian piper betle L. variants - Osman, Muhamad Faris; Lee, Soo Yee; Sarbini, Shahrul Razid; Mohd Faudzi, Siti Munirah; Khamis, Shamsul; Zainudin, Badrul Hisyam; Shaari, Khozirah (MDPI AG, 2021)
The differences in pungency of “sirih” imply the probable occurrence of several variants of Piper betle L. in Malaysia. However, the metabolite profiles underlying the pungency of the different variants remain a subject of further research. The differences in metabolite profiles of selected Malaysian P. betle variants were thus investigated; specifically, the leaf aqueous methanolic extracts and essential oils were analyzed via 1H-NMR and GC-MS metabolomics, respectively. Principal component analysis (PCA) of the 1H-NMR spectral data showed quantitative differences in the metabolite profiles of “sirih melayu” and “sirih india” and revealed an ambiguous group of samples with low acetic acid content, which was identified as Piper rubro-venosum hort. ex Rodigas based on DNA sequences of the internal transcribed spacer 2 (ITS2) region. The finding was supported by PCA of two GC-MS datasets of P. betle samples obtained from several states in Peninsular Malaysia, which displayed clustering of the samples into “sirih melayu” and “sirih india” groups. Higher abundance of chavicol acetate was consistently found to be characteristic of “sirih melayu”. The present research has provided preliminary evidence supporting the notion of occurrence of two P. betle variants in Malaysia based on chemical profiles, which may be related to the different genders of P. betle.